Handling, throws, catches and collaborations in elite group rhythmic gymnastics - Avila-Carvalho, L.; Klentrou, P.; Lebre, E. (Science of Gymnastics Journal, 2012)
Apparatus technique is crucial in the Rhythmic Gymnastics (RG) performance evaluation because of its high impact on the final score and it is the particular requirement of this sports. The technical vigour required in the use of apparatus evidences the need to study the composition of high level routines. An analysis of the apparatus work in high level group routines will give a new insight in the understanding of RG. With this in mind, we used the groups` composition forms submitted during the Portimão World Cup series from 2007 to 2010 to analyse the apparatus difficulty profile of the RG high level group routines. A total of 126 group routines from 28 countries were analysed. It is concluded that hoop routines had the most balanced apparatus technique whereas the poorest technical apparatus work was seen in clubs maybe because is the only double apparatus. According to the competition success analysis, success in high level RG group competition could be explained by: higher training volume (hours per week) (43%), higher use of throws (6%) and collaborations with risk (16,5%). These risky technical elements performed by the higher level groups require an anticipation coincidence ability that is linked with the loss of visual contact with the apparatus.